2002
DOI: 10.1046/j.1365-2842.2002.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of horizontal and vertical overlap with prevalence of temporomandibular disorders

Abstract: The aim of the study was to evaluate the relationship between horizontal (HO) and vertical overlap (VO) and prevalence of temporomandibular disorders (TMD) in a non-patient population. Out of the total number of subjects (230), 65.7% subjects were classified as asymptomatic, 5.7% subjects had muscle disorders (MD) (myalgia), 9.1% subjects had disc displacement with reduction (DDR), while 19.6% subjects had disc displacement with reduction associated with muscle disorder (DDR + MD) (myalgia). The HO equal to or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The inclusion criteria were (1) diagnosis of having myofascial pain in the TMJ, with or without limited opening and bilateral pain, for at least 6 months, according to the Research Diagnostic Criteria for Temporomandibular Disorders 28 ; (2) a positive response to the anamnesic index for TMD 29 ; (3) age between 18 and 50 years; (4) presence of local and referred pain after manual pressure of tense bands in the masseter muscles 30 ; (5) restricted mobility in the anterior-posterior condilar mobility test 31 ; and (6) restricted mobility of the first cervical vertebrae (C1) in the cervical flexion-rotation test. [32][33][34] The exclusion criteria were (1) a previous cervical whiplash; (2) severe traumatisms, surgery, and/or fractures in the mandibular condyle, TMJ, craniofacial region, and/or any spinal level; (3) degenerative, systemic, rheumatic, or tumoral disorders; (4) being under psychiatric treatment; (5) having received manual therapy within eight weeks before data collection; (6) being under orthodontic treatment; and (7) consumption of analgesics or anti-inflammatory drugs within 48 hours before the study.…”
Section: Sample and Study Proceduresmentioning
confidence: 99%
“…The inclusion criteria were (1) diagnosis of having myofascial pain in the TMJ, with or without limited opening and bilateral pain, for at least 6 months, according to the Research Diagnostic Criteria for Temporomandibular Disorders 28 ; (2) a positive response to the anamnesic index for TMD 29 ; (3) age between 18 and 50 years; (4) presence of local and referred pain after manual pressure of tense bands in the masseter muscles 30 ; (5) restricted mobility in the anterior-posterior condilar mobility test 31 ; and (6) restricted mobility of the first cervical vertebrae (C1) in the cervical flexion-rotation test. [32][33][34] The exclusion criteria were (1) a previous cervical whiplash; (2) severe traumatisms, surgery, and/or fractures in the mandibular condyle, TMJ, craniofacial region, and/or any spinal level; (3) degenerative, systemic, rheumatic, or tumoral disorders; (4) being under psychiatric treatment; (5) having received manual therapy within eight weeks before data collection; (6) being under orthodontic treatment; and (7) consumption of analgesics or anti-inflammatory drugs within 48 hours before the study.…”
Section: Sample and Study Proceduresmentioning
confidence: 99%
“…Other than crossbite, the relationships between TMD and openbite, increased overjet, and reverse overjet have also been analyzed; in some studies, these malocclusions have been related to TMDs. [22][23][24] Anterior openbite has been reported to be a risk factor that could prevent the normal functioning of a regular joint. 23,25 It was also claimed that anterior openbite aggravated myofascial pain.…”
Section: Role Of Malocclusion In Tmdsmentioning
confidence: 99%
“…Another malocclusion related to TMD is deepbite. 24,29,30 In the presence of minimal overjet with deepbite, at the beginning of mouth opening, translation of the condyle is inhibited and, because of its pure rotation, the superior lateral pterygoid muscle stretches, causing it to be ineffective in stabilizing the disk. Thus, movement of the disk to a lateral position may occur, causing a click sound.…”
Section: Role Of Malocclusion In Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies, the relationship between increased vertical overlap between anterior teeth and TMD has been analyzed . Some investigators have reported a positive association between increased vertical overlap and TMD signs and symptoms . In contrast, other studies did not find any relationship between these variables .…”
mentioning
confidence: 99%